2021
DOI: 10.1287/isre.2021.0993
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Observational Learning in Social Networks: Theory and Experimental Evidence

Abstract: The unprecedented growth of social network users in the last decade has resulted in significant increases in the availability of individual-specific information such as holiday pictures, mobile check-ins at restaurants, and information on everyday purchases. Consumers shopping through social network channels are increasingly using this information in making their purchase decisions. We find that social ties impact the magnitude of observational learning. In the case of strangers, the effect of learning is stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 90 publications
0
13
0
2
Order By: Relevance
“…En segundo lugar, el E-commerce y el Marketing Online (EMO) cuenta con 3 elementos principales, estos son las creencias de gestión, actividades de iniciación y actividades de implementación, el grado de EMO es influenciado por la ventaja relativa que el consumidor percibe y por la presión que este mismo ejerce mediante su poder adquirido gracias a las redes sociales [17]. Asimismo, en los bienes que se diferencian por su calidad, es más efectivo cuando algún extraño le hace conocer al consumidor sobre el producto, mientras que en los bienes que se diferencian por la conveniencia de su obtención, es más efectivo que alguna persona cercana, como un familiar o amigo, le haga saber al consumidor sobre el producto [18].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En segundo lugar, el E-commerce y el Marketing Online (EMO) cuenta con 3 elementos principales, estos son las creencias de gestión, actividades de iniciación y actividades de implementación, el grado de EMO es influenciado por la ventaja relativa que el consumidor percibe y por la presión que este mismo ejerce mediante su poder adquirido gracias a las redes sociales [17]. Asimismo, en los bienes que se diferencian por su calidad, es más efectivo cuando algún extraño le hace conocer al consumidor sobre el producto, mientras que en los bienes que se diferencian por la conveniencia de su obtención, es más efectivo que alguna persona cercana, como un familiar o amigo, le haga saber al consumidor sobre el producto [18].…”
Section: Discussionunclassified
“…El aprender de extraños es más efectivo para los productos diferenciados verticalmente que para los productos diferenciados horizontalmente, los minoristas en línea que ofrecen productos diferenciados horizontalmente tienen fuertes incentivos para cooperar con las plataformas de redes sociales y para alentar a los clientes a compartir su información de compra [18].…”
Section: Las Redes Sociales En Las Empresasunclassified
“…Our study is also related to studies on information acquisition. Information advantage on demand, product quality, and cost reduction can benefit a member of a supply chain (Gardete & Guo, 2021; Sun et al, 2019), so firms may attempt to acquire it (Cao et al, 2020; Guan & Chen, 2017; Qiu et al, 2021). A firm can obtain demand information by conducting market research (Shang et al, 2015; Shi, 2015), developing data acquisition technology (e.g., consumer scanning technology) (Guo, 2009; Shi et al, 2021), or by going through third‐party data service providers (Guan & Chen, 2017; Hao et al, 2018; Jiang et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research indicates the coexistence of the herding effect and other factors rather than focusing solely on the herding effect. The herding phenomenon is present in social media word‐of‐mouth (Jin et al, 2020; Li & Wu, 2018; Tian et al, 2021) and social network activities (Lee et al, 2015; Liu et al, 2015; Mattke et al, 2020; Qiu et al, 2018, 2021; Sunder et al, 2019; Xu & Liu, 2019). For instance, Chen et al (2011) identified the interaction effect of observational learning and word‐of‐mouth in e‐commerce.…”
Section: Literature Reviewmentioning
confidence: 99%